Les Députés du Nord de l’Angleterre et la question constitutionnelle écossaise : entre crainte et résignation - Edwige Camp-Pietrain (Revue Française de Civilisation Britannique)
Since the 1970s, Scottish constitutional issues have been on the agenda in the UK, first with the devolutionary process then with the referendum on Scotland's independence. MPs from the North of England have criticized these developments while proving unable to stop them. This paper, mostly based on their speeches during parliamentary debates held on these topics, aims at mapping out their changing arguments over four decades.